Developing Menstrual Pain Relief Underwear (CEDARRIS) for the Comfort of Menstruating Women - Erica Vidya Zihan Pertiwi; Happy Dwi Aprilina; Samsiah Mat (UM Purwokerto Press, 2024)
Background: Menstrual pain or dysmenorrhea often disrupts women's physical comfort. Interventions are needed to alleviate dysmenorrhea by designing special underwear for menstrual pain relief, aiming to reduce menstrual pain and enhance the comfort of menstruating women. Method: This research employed the Research and Development (RD) methodology, comprising ten stages: Stage I (problem potential), Stage II (data collection), Stage III (product design), Stage IV (design validation), Stage V (product revision), Stage VI (product trial), Stage VII (product revision), Stage VIII (wearability trial), Stage IX (product revision), and Stage X (mass production). Due to time constraints, the researcher has condensed the stages into 6 steps. Respective experts conducted product trials. Wearability trials involved sixth-semester nursing students at the Faculty of Health Sciences, Universitas Muhammadiyah Purwokerto. Results: : The clothing expert scored 47 and 46 in the expert development test, signifying